واقع التسويق الرقمي في المؤسسات الناشئة في الجزائر-دراسة حالة مؤسسة "يسير" - سحاري، سلاف; صالحي، فتيحة (University Of Eloued جامعة الوادي, 2024)
يهدف هذا البحث إلى الكشف عن واقع التسويق الرقمي في المؤسسات الناشئة في الجزائر، وقد تم أخذ مؤسسة "يسير" نموذجا، اعتمدت الدراسة على المنهج الوصفي التحليلي من خلال استقراء وتحليل الدراسات والأبحاث والكتب التي ترتبط بالموضوع، توصلت الدراسة إلى جملة من الاستنتاجات أهمها: تزايد وعي المؤسسات الناشئة بأهمية التسويق الرقمي، حيث تعتبر مؤسسة"يسير" من المؤسسات الناشئة الرائدة في استخدام التكنولوجيا المتطورة ؛ إلا أنه توجد عدة تحديات ومشكلات منها: ضعف البنية التحتية الرقمية ونقص الخبرة في مجالات التسويق الرقمي، قدمت الدراسة عدة توصيات منها: تحسين البنية التحتية الرقمية لتحفيز التوسع في الخدمات الرقمية، توفير برامج تدريب مستمرة للموظفين في مجالات التسويق الرقمي، مثل: تحليل البيانات، إدارة المحتوى والتسويق عبر وسائل التواصل الاجتماعي Abstract: This research aims to reveral to extent of the reality of digital marketing for startups in Algeria, the “Yassir” start-up was taken as a model, the study relied on the descriptive analytical approach through extrapolation and and analysis of studies, research and books related to the subject, the study reached a number conclutions, the most important of wich is: Startups are increasingly aware of the importance of digital marketing, and Yessir is one of the leading start-ups in using advanced technology; However, there are several challenges and problems, including: weak digital infrastructure and lack of experience in the fields of digital marketing. The study presented several recommendations, including: improving the digital infrastructure to stimulate the expansion of digital services, providing continuous training programs for employees in the fields of digital marketing, such as: data analysis, content management and marketing via social media.
The reality of digital marketing in Startup s in Algeria - a case study of the "Yassir" Startup
مداخلة
Keywords: التسويق الرقمي; المؤسسات الناشئة; مؤسسة "يسير"; Digital Marketing; Startups; Yassir Startup